Penerapan Metode Perhitungan Pajak Pertambahan Nilai Terutang Di Indonesia - Setiadi Alim Lim (BIP's JURNAL BISNIS PERSPEKTIF, 2014)
Conceptually, there are three methods that can be used to calculate the Value Added Tax payable: the invoice credit method, subtraction method and addition method. Of the three methods is the most widely used by countries in the world that uses a System of Value Added Tax is the invoice credit method. Law on Value Added Tax in Indonesia is not explicitly stated using a certain method in calculating the Value Added Tax payable. However, when examined Law of Value Added Tax and its implementing regulations, the calculation of the Value Added Tax payable in Indonesia uses the three methods mentioned above. Implementation of the invoice credit method reflected from the use crediting Input Tax using tax invoice to Output Tax. The application of subtraction method can be seen from the use of method for crediting Input Tax calculation and use of other values. Then the application of addition method can be seen from the imposition of Value Added Tax to build their own activities.